305 Improving Clinic DNA Rates with a Patient Initiated Follow Up Pathway: A Cohort Study. (19th August 2022) - Katsura, C; Tomouk, T; Gathura, E; Miranda, BH; Zweifel, CJ
Abstract: Introduction: A Patient Initiated Follow-Up (PIFU) pathway was implemented in 2019; this enabled patients with specific plastic surgery trauma diagnoses to request a consultant clinic review within 3 months, without a routine follow-up appointment being made. PIFU aims to reduce 'did not attend' (DNA) rates in line with the Royal College of Surgeons of England Outpatient Clinics Guide. Aim: To assess the impact of PIFU on DNA rates of plastic surgery trauma clinics. Method: A prospective cohort study of plastic surgery PIFU outpatient clinic DNA rates was undertaken (1 st January–31 st October 2021) and compared to data held for pre-PIFU pathway DNA rates (1 st January–30 th June 2018); inclusion dates for 2021 were extended to achieve comparable sample sizes for patient numbers routinely booked into clinics. DNA rates were collected from the hospital clinic database. Data were analysed using IBM®SPSS®. The Kolmogorov-Smirnov test was performed to assess sample population distribution, and the Chi 2 test was used to compare categorical data. Results: A total of 1702 patients were included in the study. Pre-PIFU, there was an 18% (149/823) DNA rate for patients (31.4 years ± 18.45 years) (mean age ± SD) booked into routine Consultant clinic follow-up. Post-PIFU, there was a 9% (77/879) DNA rate for patients (31.1 years ± 20.77 years) booked into routine Consultant clinic follow-up. This represents a significant reduction in DNA rates by 9% (Chi 2 =7.49, p<0.01); non-operatively managed hand fracture patients were the most frequent non-attenders. Conclusions: The PIFU pathway has significantly reduced trauma clinic DNA rates.